Identification and Functional Verification Reveals that miR-195 Inhibiting THRSP to Affect Fat Deposition in Xinyang Buffalo - Wang, Shuzhe; Pan, Cuili; Ma, Xiaojie; Yang, Chaoyun; Tang, Lin; Huang, Jieping; Wei, Xuefeng; Li, Hui; Ma, Yun (Frontiers in Genetics, 2021)
The buffalo population is extensive in China, but its meat quality is relatively inferior. Therefore, improving meat quality should be one of the breeding goals. microRNAs (miRNAs) play an essential regulatory role in the post-transcriptional expression of genes. Some studies have reported their function regulating genes related to fat deposition and adipocyte differentiation in cattle, but there is limited reports in buffalo. We performed small RNA transcriptome sequencing of Xinyang buffalo adipose tissue between calves and adults in this study. As a result, 282 mature miRNAs were significantly differentially expressed, and co-expression analysis showed that 454 miRNAs were significantly associated with developmental stages. Target gene identification, GO (gene ontology) annotation, and KEGG analysis of miRNAs showed that miR-195, miR-192, and miR-24-3p could target key genes for lipogenesis and thus regulate adipose deposition and differentiation. Among them, miR-195 was significantly upregulated in adipose tissue and induced adipocytes of adult buffaloes, and its overexpression significantly inhibited lipid accumulation in primary adipocytes. Dual-luciferase reporter gene analysis showed that miR-195 reduced the expression of thyroid hormone response protein (THRSP) by targeting its 3′ untranslated terminal region, suggesting that miR-195 may inhibit lipid accumulation in adipocytes by regulating THRSP. The results confirmed the reliability of predictive screening of miRNAs and provided theoretical support for buffalo fattening.